1999
DOI: 10.1046/j.1471-4159.1999.0720338.x
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Transfer of 2‐Docosahexaenoyl‐1‐Lysophosphatidylcholine Through an In Vitro Blood‐Brain Barrier Over Unesterified Docosahexaenoic Acid

Abstract: Abstract:The passage of either unesterified docosahexaenoic acid (DHA) or lysophosphatidylcholine-containing DHA (lysoPC-DHA) through an in vitro model of the blood-brain barrier was investigated. The model was constituted by a brain capillary endothelial cell monolayer set over the medium of an astrocyte culture. Cells were incubated for 4 h with a medium devoid of serum, then the endothelial cell medium was replaced by the same medium containing labeled DHA or lysoPC-DHA and incubations were performed for 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
48
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 82 publications
(50 citation statements)
references
References 48 publications
2
48
0
Order By: Relevance
“…2 Docosahexaenoic acid (DHA) (22:63) is a polyunsaturated fatty acid uniquely enriched in the brain and retina, especially in synaptic membranes and in photoreceptor cells (8 -10). Astrocytes play an important role in the delivery of DHA to the blood-brain barrier endothelial cells and to neurons (11,12). Although the physiologic basis for why DHA is enriched in the brain and retina remains unclear, reduced levels of DHA are associated with disturbances in visual acuity, behavior, and learning in young animals and humans (13)(14)(15).…”
mentioning
confidence: 99%
“…2 Docosahexaenoic acid (DHA) (22:63) is a polyunsaturated fatty acid uniquely enriched in the brain and retina, especially in synaptic membranes and in photoreceptor cells (8 -10). Astrocytes play an important role in the delivery of DHA to the blood-brain barrier endothelial cells and to neurons (11,12). Although the physiologic basis for why DHA is enriched in the brain and retina remains unclear, reduced levels of DHA are associated with disturbances in visual acuity, behavior, and learning in young animals and humans (13)(14)(15).…”
mentioning
confidence: 99%
“…These results clearly showed that LysoPC-DHA is a privileged form of transport of DHA to the brain. We also showed that preference for 1-Lyso-2-DHA-PC by using an in vitro model of BBB (constituted by brain-capillary endothelial cell and astrocyte co-cultures) compared to nonesterified DHA (Bernoud et al, 1999). The preferential uptake of DHA from LysoPC-DHA has been recently corroborated with the discovery of a protein expressed in the BBB, Mfsd2a allowing specific uptake of LysoPC (Nguyen et al, 2014;Quek et al, 2016).…”
mentioning
confidence: 53%
“…We previously showed that 1-lyso,2-docosahexaenoyl-glycerophosphocholine (LysoPC-DHA) is a preferred physiological carrier of DHA to the brain (Thies et al, 1994;Bernoud et al, 1999). DHA, either as nonesterified fatty acid (NEFA) or esterified at the sn-2 position of LysoPC, were bound to albumin and injected into the rat to look at the brain accretion.…”
mentioning
confidence: 99%
“…Among the studied PUFA, DHA from LysoPC-DHA was the most highly taken up (10-fold) compared with its non-esterified form, a preference that was not found for the uptake of DHA by other organs such as the heart, kidney and liver (Thiès et al, 1994). Furthermore, the use of a re-constituted blood-brain barrier allowed to confirm that DHA provided in LysoPC was more efficient to cross this barrier than non-esterified DHA (Bernoud et al, 1999). Interestingly, a very recent work has demonstrated that the blood-brain barrier expresses a specific protein that specifically binds LysoPC-DHA (Nguyen et al, 2014), which may explain the preferential uptake of DHA when esterified in LysoPC.…”
Section: Introductionmentioning
confidence: 96%